How to manage Informal Workers of Yellow Troops in Surabaya City building OCB? - Jum'ati, Nurleila; Nuraini, Anggita Aulia; Rahmandiansyah, Fajar; Mahendra, Almadyah Putri; Nazarudin, Faisal Fikri; Anggraeni, Meita (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research Aim : This study aims to determine the pattern of management in the Surabaya City Government towards Surabaya city cleaning officers (street sweepers), known as yellow troops. Design/Method/Approach : Data were collected through interviews and observations. The informant was the person in charge of the yellow troop, namely the Garbage Cleaning Sub-Coordinator. Documentation data is used as secondary data to strengthen the data and support qualitative descriptive analysis. Research Finding : The author finds that financial rewards are not the only way in the management pattern carried out by the Surabaya city government for informal workers in the yellow troops. The management pattern developed by the Surabaya city government is to strengthen non-financial rewards for the yellow troops and supervision is carried out in stages so that appropriate and sustainable supervision is obtained. Theoretical contribution/Originality : OCB character research is generally carried out using quantitative research methods, not much is done with qualitative research methods, and is carried out in city and district cleaning workers as informal workers. Practitionel/Policy implication : The findings show that city and district governments in Indonesia need to understand in building and maintaining OCB character in informal workers, especially yellow troops or street sweepers by implementing appropriate and sustainable non-financial rewards and supervision. One of the non-financial rewards is the existence of a career path and punishment because of supervision. Research limitation : The research conducted was limited to the management of street sweepers in Surabaya city.